New Horizons in Food Science via Agricultural Immunity - Van Eden, Willem; Nochi, Tomonori; Pieterse, Corné M. J. (Frontiers Media SA, 2020)
Agricultural immunology is a new research field that fuses animal, marine and plant immunology, all of which have been previously regarded as separate topics and fields. Recent progresses in immunological research, however, have demonstrated that the innate immune system against agricultural infection causing pathogens has common features in plants and animals. Agricultural Immunology therefore aims to plant the seeds for developing drug-independent safe food production systems by modulating these innate immune system. Animals and plants face constant risk of infection with biologically diverse pathogens that can cause serious diseases.